FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016) - Awaliani Akmalia, 14.05.52.0235; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2018)
This Study aimed to analyze and verify the influence of the profitability, liquidity, leverage, company size, audit opinion, and ownership structure on the timeliness of financial reporting. The population in this study are all mining companies listed on the Indonesia Stock Exchange in 2014 until 2016. The sample of this study was taken by using purposive sampling technique, so that these were 58 companies got for this study. Data analysis tools used in this research is regression logistic. The result of this study showes that liquidity and ownership structure does not affect on financial reporting. Which. The profitability, leverage, and company size significant negative influence on financial reporting.Keywords :Profitability, liquidity, leverage, company size, audit opinion, and ownership structure